Appreciation and Self-Actualization of Employee Performance at the Governance Secretariat, Jember District - Imam Abrori; Via Lailatur Rizki (International Journal of Marketing & Human Resource Research, 2022)
The research with the title Of Award and Self-Actualization of Its Relationship to Employee Performance of The Regional Governance Section of Jember District aims to analyze the effect of appreciation and self-actualization on employee work performance at the Secretariat of Regional Governance Kab. Jember partially and simultaneously. The number of samples used in the study was 35 people with census sampling techniques. The data collection methods used in this study used questionnaires, interviews, and library studies. The analysis used includes validity test, reliability test, multiple linear regression analysis, multicolonierity test, heteroskedasticity test, partial test normality test, simultaneous test and determination coefficient test. From the results of multiple linear regression analysis using the partial test states that there is a positive and significant influence between the reward variables on work performance. The results of the partial test also stated that there was a positive and significant influence among the variables of self-actualization on work performance. The results of multiple linear regression analysis using the simultaneous test state that there is a positive and significant influence between reward variables and self-actualization on work performance.